Commentary. Oligognostic mega-analysis. Is Archie turning in his grave?. Issue 4 (August 2015) - Shapiro, Samuel
Highlights Cochrane centers that undertake meta-analyses and systematic reviews have been established worldwide. The meta-analysis of observational studies is seldom valid because of bias, confounding, variable methodology, and lack of transparency. The meta-analysis of well-conducted short-duration clinical trials can be valid and informative. The meta-analysis of long-duration trials is seldom valid because of "unblinding" and losses to follow-up. Systematic reviews of qualitative evidence are not superior to well-conducted conventional reviews.